(untitled) (Global Journal of Science Frontier Research, 2012)
The thin-layer drying characteristics of carrot slices were investigated under four microwave powers; 200, 300, 400 and 500 W and slice thickness of 2.5 mm. Data were analyzed to obtain diffusivity values from the period of falling drying rate. Four mathematical models for describing the thin-layer drying behavior of carrot were investigated. The results show that the Midilli et al. is the most appropriate model for drying behaviour of thin layer carrot slices. An analysis of variance (ANOVA) revealed that microwave power significantly affected the drying time, drying rate, effective diffusivity and specific energy consumption. The effective diffusivity varied from 1.90×10 -8 to 3.99×10 -8 m 2 /s, and the activation energy was determined to be 36.40. Specific energy consumption values ranged 8.58 to 12.46 MJ/kg and the optimized specific energy consumption was obtained 540 W microwave levels.